Pengaruh Pendidikan dan Status Sosial Ekonomi Kepala Keluarga bagi Kesehatan Lingkungan Masyarakat - Mbina Pinem (Universitas Medan Area, 2016)
This paper aims to investigate the influence of education and socioeconomic status of the family head of the environmental health community. Such educational factors influencing knowledge about the family head of environmental health. Revenue also greatly affect each household about the health of the environment. Employment / livelihoods also influences knowledge about environmental health chief. Social status greatly affects the environmental health held where if the higher the socioeconomic status of the family head nice views of education, employment and work / livelihood, the better the health of the environment that is held. That the head of the family socioeconomic status (education, income and employment / livelihood) contributed greatly that a significant difference between the socioeconomic status of the family head